Study on the Preparation of Biscuit and Cake from Amaranthus and Sorghum - Karki, Roman (Journal of Food Science and Technology Nepal, 2016)
Biscuit and cake are prepared from amaranthus and sorghum flour at the proportion of 20, 30, 40 and 50% with wheat flour. Sensory evaluation was carried out and there is no significant difference (p≤0.05) in texture in the different biscuit made from amaranthus flour. However there is significant difference in color, taste, smell and overall acceptance in amaranthus biscuits. In case of sorghum biscuit there is significant difference in texture and no significant difference in color, taste, smell and overall acceptance. Similarly, there is significant difference in color, texture, smell, taste and overall acceptance between amaranthus cakes. However, there is significant difference in color of sorghum cake and the difference is insignificant in texture, taste, smell and overall acceptance.